Deglobalization and talent sourcing: Cross‐national evidence from high‐tech firms. Issue 2 (29th September 2020) - Farndale, Elaine; Thite, Mohan; Budhwar, Pawan; Kwon, Bora
Abstract: As corporate globalization is restricted through changes in macro‐environments, firms traditionally reliant on global talent pools are suffering. This is particularly true for high‐tech firms' seeking to source high‐skilled STEM (science, technology, engineering, and mathematics) talent. The aim of this study, in line with the special issue, is to explore the impact of macro‐level trends in national government policy and political climates on high‐tech firms seeking to source high‐skilled STEM talent. By applying coevolutionary reasoning, we develop propositions that link the macro environment with corporate strategizing. A multi‐respondent, qualitative research design is adopted, involving interviews and focus groups with 40 practitioners and industry experts. Through qualitative data analysis, we identify emergent adaptations to corporate talent sourcing activities for dealing with increasing STEM shortages linked to deglobalization. As the data highlight, the adaptations are a consequence of both internal strategic factors as well as external institutional forces and the interplay between the two. Implications for future research and practice are discussed.